Superior mesenteric aneurysm associated with median arcuate ligament syndrome and a single celiacomesenteric trunk - Drew J. Braet, MD; Kian Pourak, BS; Frank M. Davis, MD; Jonathan L. Eliason, MD; Chandu Vemuri, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
Median arcuate ligament syndrome (MALS) is known to promote arterial collateral circulation development from mesenteric vessel compression and can lead to the development of visceral aneurysms. These aneurysms are often diagnosed at the time of rupture and pose a significant morality risk without appropriate intervention. A celiacomesenteric trunk is a rare anatomic variant in which the celiac artery and superior mesenteric artery share a common origin and has been postulated as a risk factor for developing MALS. In this report, we present a novel case of MALS in a patient with a celiacomesenteric trunk and a superior mesenteric artery aneurysm.